2018
DOI: 10.1177/0739532918761065
|View full text |Cite
|
Sign up to set email alerts
|

Social credibility online: The role of online comments in assessing news article credibility

Abstract: This 2 × 2 experimental study (N = 196) tested the effects of source expertise and opinion valence in readers’ comments on the credibility of an online news story about genetically modified organisms (GMOs). Source expertise had a significant influence on perceptions of article credibility; articles were judged more credible when public comments embedded in the story were from expert sources (e.g., scientists) rather than nonexpert sources (e.g., Twitter users). Effects were larger on high-frequency news users… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
(13 reference statements)
0
10
0
2
Order By: Relevance
“…Others have found that exposing news audiences to expert opinions, as opposed to the opinions of other social media users, led to higher perceptions of news credibility (Pjesivac, Geidner, & Cameron, ). However, that work examined the opinions embedded in a sidebar of a news article (i.e., seen alongside the text of an article), which are different than comments seen on a Facebook post advertising a story and seen before reading the news article.…”
Section: Discussionmentioning
confidence: 99%
“…Others have found that exposing news audiences to expert opinions, as opposed to the opinions of other social media users, led to higher perceptions of news credibility (Pjesivac, Geidner, & Cameron, ). However, that work examined the opinions embedded in a sidebar of a news article (i.e., seen alongside the text of an article), which are different than comments seen on a Facebook post advertising a story and seen before reading the news article.…”
Section: Discussionmentioning
confidence: 99%
“…There are several previous methods for analyzing and evaluating the performance of websites from different domains [5,[7][8][9][10][11][12][13][15][16][17][18][19]. These methods mostly evaluate the website as an interface and study different aspects such as website's design, content, accessibility, and usability [5] and have been used for various domains such as ecommerce websites [13], e-government websites [82], agritourism websites [21], tourism management [22], library websites [23] and news websites [5,[24][25][26].…”
Section: Related Workmentioning
confidence: 99%
“…While the connections between systems of heuristic credibility cues and the perception of credibility seem obvious, much of the literature focuses on a checklist approach to researching how cues affect the perception of credibility. Studies isolate heuristics such news brand names (Metzger, 2007;Sundar & Nass, 2001), source credibility (Pjesivac, Geidner & Cameron, 2018), platform publisher (Bhandari, 2018), number of social recommendations (Xu, 2013), or website features (Flanagin & Metzger, 2007) to find the effects of cues on the perception of credibility.…”
Section: News Credibilitymentioning
confidence: 99%